Urinary bladder Leiomyoma – a rare case report - H U Bhuiyan (IMC Journal of Medical Science, 2008)
A rare case of urinary bladder leiomyoma in a female patient is presented here. A quarter of these cases are asymptomatic only to be diagnosed by ultrasonography. Symptomatic cases are also misleading as in this case. Laparotomy, removal of mass and ultimately histopathology proved the case to be that of a urinary bladder leiomyoma.